Efficacy of Sphinkeeper™ implant in treating faecal incontinence. Issue 5 (17th February 2020) - Litta, F; Parello, A; De Simone, V; Campennì, P; Orefice, R; Marra, A A; Goglia, M; Moroni, R; Ratto, C
Graphical Abstract: The primary aim of this prospective study was to assess the efficacy of Sphinkeeper™ (SK) implantation in patients with faecal incontinence. Forty-two patients with faecal incontinence (14 with sphincter defects) underwent SK implantation and were followed up for a mean(s.d.) of 15·9(8·6) months. SK implantation was a safe and effective method that improved patients' quality of life. Implants and incontinence